2015
DOI: 10.1108/ijmhsc-02-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuses of left-behind children of migrant women: community-perceived vulnerabilities and barriers in prevention

Abstract: Purpose – The purpose of this paper is to describe hitherto unexplored issues related to sexual abuse of left-behind children of migrant women in Sri Lanka. Design/methodology/approach – This qualitative study was conducted in high labour-sending districts. Focus group discussions (FGDs) were conducted with school teachers, community youth groups and members of civil organisations, and semi-structured interviews (SSIs) were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
0
0
1
Order By: Relevance
“…In this study, it was found that girls have a higher prevalence of CSA compared to boys in all types of CSA; this is in line with Tanaka's (2017) systematic review research in Japan [34]. Characteristics of girls such as shyness, obedience, and fear of stigmatization have an important role in increasing CSA in girls [52]. The lower prevalence of CSA in boys than in girls is possible due to underreporting and the absence of data on CSA prevalence among MSM [28], [50].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, it was found that girls have a higher prevalence of CSA compared to boys in all types of CSA; this is in line with Tanaka's (2017) systematic review research in Japan [34]. Characteristics of girls such as shyness, obedience, and fear of stigmatization have an important role in increasing CSA in girls [52]. The lower prevalence of CSA in boys than in girls is possible due to underreporting and the absence of data on CSA prevalence among MSM [28], [50].…”
Section: Discussionsupporting
confidence: 87%
“…Varios estudios han identificado que en muchos países las instituciones psicosociales estatales y no estatales y el personal autorizado son percibidas como inadecuadas en su papel de protección de los niños y niñas víctimas de violencia 17 , lo que da lugar a una baja denuncia y cooperación comunitaria 18,19 . Las instituciones a veces muestran renuencia a denunciar posibles casos debido a la preocupación de hacer acusaciones falsas o represalias por parte del victimario 20 .…”
Section: Introductionunclassified